tRNA-Derived Fragments (tRFs): Emerging New Roles for an Ancient RNA in the Regulation of Gene Expression - Simon P. Keam; Gyorgy Hutvagner (Life, 2015)
This review will summarise the recent discoveries and current state of research on short noncoding RNAs derived from tRNAs—known as tRNA-derived fragments (tRFs). It will describe the features of the known subtypes of these RNAs; including sequence characteristics, protein interactors, expression characteristics, biogenesis, and similarity to canonical miRNA pathways. Also their role in regulating gene expression; including mediating translational suppression, will be discussed. We also highlight their potential use as biomarkers, functions in gene regulation and links to disease. Finally, this review will speculate as to the origin and rationale for the conservation of this novel class of noncoding RNAs amongst both prokaryotes and eukaryotes.